Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
[tex]x^2+y^2+4x-6y+12=0 \\
y^2-6y+9=-x^2-4x-3\\
(y-3)^2=-x^2-4x-3\\
y-3=\sqrt{-x^2-4x-3} \vee y-3=-\sqrt{-x^2-4x-3}\\
y=3+\sqrt{-x^2-4x-3} \vee y=3-\sqrt{-x^2-4x-3}[/tex]
[tex]x^2+y^2+4x-6y+12=0\\\\x^2+2x\cdot2+2^2+y^2-2y\cdot3+3^2-2^2-3^2+12=0\\\\(x+2)^2+(y-3)^2-4-9+12=0\\\\(x+2)^2+(y-3)^2-1=0\\\\(y-3)^2=1-(x+2)^2\\\\(y-3)^2=[1-(x+2)][1+(x+2)]\\\\(y-3)^2=(-x-1)(x+3)\\\\y-3=\sqrt{-(x+1)(x+3)}\\\\y=3+\sqrt{-(x+1)(x+3)}[/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.